Examining the effectiveness of intrathecal baclofen on spasticity in individuals with chronic spinal cord injury: A systematic review. (January 2014) - McIntyre, Amanda; Mays, Rachel; Mehta, Swati; Janzen, Shannon; Townson, Andrea; Hsieh, Jane; Wolfe, Dalton; Teasell, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> Objective To review the available evidence on the effectiveness of intrathecal baclofen in the treatment of spasticity in individuals with spinal cord injuries (SCIs) at least 6 months post-injury or diagnosis. Data sources A literature search of multiple databases (Pub Med, CINAHL, EMBASE) was conducted to identify articles published in the English language. Study selection Studies were included for review if: (1) more than 50% of the sample size had suffered a traumatic or non-traumatic SCI; (2) there were more than three subjects; (3) subjects received continuous intrathecal baclofen via an implantable pump aimed at improving spasticity; and (4) all subjects were ≥6 months post-SCI, at the time of the intervention. Data extraction Data extracted from the studies included patient and treatment characteristics, study design, method of assessment, and outcomes of the intervention. Data synthesis Methodological quality was assessed using the PEDro for randomized-controlled trials (RCTs) and the Downs and Black (D&B) tool for non-RCTs. A level of evidence was assigned to each intervention using a modified Sackett scale. Conclusion The literature search resulted in 677 articles. No RCTs and eight non-RCTs (D&B scores 13–24) met criteria for inclusion, providing a pooled sample size of 162 individuals. There was substantial level 4 evidence that intrathecal baclofen is effective in reducing spasticity. Mean Ashworth scores reduced from 3.1–4.5 at baseline to 1.0–2.0 (P < 0.005) at follow-up (range 2–41 months). Average dosing increased from 57–187 µg/day at baseline to 218.7–535.9 µg/day at follow-up. Several complications from the use of intrathecal baclofen or pump and catheter malfunction were reported.